MEASURING THE EFFECTIVENESS OF HEALTH MEDIA IN THE SOCIAL MEDIA DURING THE CORONA PANDEMIC A SURVEY STUDY OF SOCIAL MEDIA USERS - Muntadher Khalid Abbood (European Journal of Humanities and Educational Advancements, 2022)
The current research seeks to identify the measurement of the effectiveness of health media in social media sites during the Corona pandemic, where the problem of the research was in seeking to know the effectiveness of press media on social media during the Corona pandemic and the extent of the commitment of this type of media in directing public opinion properly. The research problem of the current study was to measure the effectiveness of health media in social media sites during the Corona pandemic. In order to achieve the goal of the current research, the researcher followed the steps of the descriptive approach by constructing a questionnaire to collect data and information from a sample of followers of social media sites for media organizations, where the sample reached (100) individuals and applying the tool to the sample, the research reached the results that included the following: 1- The media is interested in dealing with and disseminating information to viewers about the Corona pandemic. 2- The media coverage in the media focuses on preventive measures that help prevent infection. 3- The media uses applied methods and models to warn of infection with the Corona virus. 4- The media sometimes cares about people with chronic diseases and tries to prevent them from getting infected. 5- The media promotes products that help prevent infection